Enfoques metodológicos en el estudio de los asentamientos fortificados de la edad del hierro : aproximación teórica a la metodología de estudio sobre la defensa del territorio en la Prehistoria Final Europea = Methodological approaches on the studies of Iron Age fortified settlement : theoretical approach to the methodology on the research about the defence of the territory during the European late prehistory /: aproximación teórica a la metodología de estudio sobre la defensa del territorio en la Prehistoria Final Europea = Methodological approaches on the studies of Iron Age fortified settlement : theoretical approach to the methodology on the research about the defence of the territory during the European late prehistory. ([2016]) - Rodríguez Monterrubio, Óscar
No abstract available